Origins, evolution and assessment of Europe-Africa relations: lessons for future partnerships - (:unkn) unknown (My University, 2023)
Africa and Europe are united by history and a particular geographical proximity. They are close neighbors, as Sicily in Italy is 145 km from Tunisia, and Morocco is only 14 km from Spain via the Strait of Gibraltar. This proximity means that Europe and Africa face the same issues and challenges (security, geostrategic, commercial, economic, developmental, environmental, migratory, demographic...) which require joint approaches to resolving them, on which the future of these two continents, and of the world as a whole, depends. At the same time, they are helping to forge a new form of strengthened partnership between African countries and new powers such as China, Russia, India and Turkey. This new context of world order, based on multilateralism and placing Africa at the center of the chessboard, is leading Europe, through a new approach, to rebuild its relations with Africa, so that the history of the 21st century is not written without it.
Keywords: African Research